1998
DOI: 10.1111/j.1523-1755.1998.00823.x
|View full text |Cite
|
Sign up to set email alerts
|

Universal precautions prevent hepatitis C virus transmission: A 54 month follow-up of the Belgian multicenter study

Abstract: The isolation of anti-hepatitis C virus (HCV) in hemodialyzed (HD) patients has been repeatedly advocated to prevent nosocomial HCV transmission. We evaluated the incidence of seroconversion for HCV in Belgian HD patients, and demonstrate the complete prevention of HCV transmission by adherence to the universal precautions advocated by the Centers for Disease Control (Atlanta, GA, USA). All (N = 963) HD patients from 15 units, none of which isolates anti-HCV positive patients, were tested by a second or third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
96
0
15

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(120 citation statements)
references
References 26 publications
9
96
0
15
Order By: Relevance
“…In our research, we verified a high frequency of male patients of 59%, corroborating with other projects in the literature [8,[19][20][21] that also demonstrate the absence of association between the gender, age, and the infection of HCV in dialysed patients [17]. As in other studies, we did not find association between the base disease and the frequency of infection by the hepatitis C virus [16,17].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our research, we verified a high frequency of male patients of 59%, corroborating with other projects in the literature [8,[19][20][21] that also demonstrate the absence of association between the gender, age, and the infection of HCV in dialysed patients [17]. As in other studies, we did not find association between the base disease and the frequency of infection by the hepatitis C virus [16,17].…”
Section: Discussionsupporting
confidence: 81%
“…In our study, we found an inferior value to the ones verified in the Brazilian studies as well as the ones from Santa Catarina State with 16.8 % of the cases of hepatitis C, despite being low, it is still worrying. The found value may be due to a decrease in the Hepatitis C prevalence already observed in other studies or it refers to reduction of the HCV infection after blood transfusion as consequence of the introduction of control measures to prevent the nosocomial transmission [18,19].…”
Section: Discussionmentioning
confidence: 96%
“…The reported prevalence of hepatitis C virus (HCV) infection ranges from 8 to 20% in dialysis patients receiving maintenance dialysis in the developed world; [1][2][3][4][5] the frequency of HCV is much higher in patients undergoing dialysis in less-developed countries. [6][7][8][9][10][11][12][13][14] Recent studies have shown that HCV is an important cause of morbidity and mortality in chronic dialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, o uso mais disseminado da eritropoetina levou a uma redução do número de hemotransfusões nessa população. Consequentemente, o interesse voltou-se para a discussão de estratégias visando à redução da transmissão do HCV entre os pacientes nos centros de diálise, a qual pode ocorrer por quebra das rotinas de precauções universais 5,6 .…”
Section: Introductionunclassified